(3GdLhgQ GdfajS jTQM efXheI GdQFjSs - (3ehSi Hf EHQGgje Hf ehSi Hf eMeO , GdeJWHH GdHZOGOjs; (3GdQFjS GHf SjfG , CHh Ydj TQa Gdedc (B: (3GdajdSha GdQFjS,J (B428 (3g` s ((3jhSa Hf eMeO Hf jhSa , GdTgjQ HGHf Gdhcjd s)
(3ChdgG (B:s
(3aGJMI GdLRA GdChd (B:_ (3hHYO (B: (3aEfg deG LeY TJGJ gPG GdYde GdfajS aQjO hgQg , hCjfYJ HhLhO aQhZg GdeJCUdg ai QhVGJ acQI s
(3BNQgG (B:s
(3BNQ GdLRA GdKGfi (B:- (3hidg hUMHg GdCNHGQ eGchQ Gddjd eY GdfgGQ hdjcf gPG BNQ eG JjSQ LeYg s
(3Je JCdjaI Sfg (B870(3g`s
(3de jKHJ YdjgG GSe eDdagGs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3JHUQI GdYfhGf (B:s
(3TQMs
Keywords: (3GdWHs